Cancer burden attributable to human papillomavirus infection by sex, cancer site, age, and geographical area in China. (12th November 2019) - Duan, Rufei; Qiao, Youlin; Clifford, Gary; Zhao, Fanghui
Abstract: Background: Human papillomavirus (HPV) attributable cancer burden is currently unknown in China, which is essential to evaluate the potential benefit of existing HPV vaccines and to inform cancer control policy. Methods: We extracted data of cancer incidence and mortality in 2014 from Chinese Cancer Registry Annual Report, and data of national population from National Bureau of Statistics. HPV‐attributable cancer burden was estimated by incorporating cancer rates and population forecasts by sex, cancer site, age and geographical area, and then combined to corresponding population attributable fractions. Results: We estimated that there were 110 894 HPV‐attributable new cancer cases in China in 2014, including 99 253 cervical cancers, 4449 noncervical cancers in females and 7192 cancers in males. The age‐standardized incidence of HPV‐attributable cancers in China was 5.69 per 100 000 persons, being slightly higher in rural than urban areas. Specifically, 51.1% of HPV‐attributable cervical cancers were diagnosed in women aged 40‐54 years, while 75.8% of noncervical cancers were diagnosed at 45‐79 years of age. Among males, 53.4% of cancers were diagnosed at 55‐74 years of age. Thirty five thousand six hundred and eighty three HPV‐attributable cancer deaths were estimated, including 29 683 due to cervical cancer, and 2307 and 3693 due to noncervical cancer in females and males, respectively. Conclusions: The cancer burden attributable to HPV in China is substantial. HPV vaccination and cervical screening should be prioritized. Abstract : Human papillomavirus (HPV) attributable cancer burden is currently unknown in China; we estimated HPV‐attributable cancer cases and deaths by sex, cancer site, age and geographical area. There is a pressing need for these data to inform evidence‐based policy with regard to HPV vaccination and screening programs.